Griefwalker [videorecording (DVD)] - Wilson, Tim, 1947- (Alive Mind ; distributed by Lorber HD Digital, 2009)
Portrayal of palliative caregiver Stephen Jenkinson. This film shows Tim Wilson's dealing with his denial of his own death where he almost succumbed to an illness, and coping with the near death of someone close to him. Jenkinson explains something that is uncomfortable for most Westerners to hear, that death and grief are woven into the fabric of life and that death is something to be 'befriended.'